Healthcare Team Perceptions of a Portal for Parents of Hospitalized Children Before and After Implementation - Kelly, Michelle M.; Dean, Shannon M.; Carayon, Pascale; Wetterneck, Tosha B.; Hoonakker, Peter L.T. (Applied Clinical Informatics, 2017)
Background. Patient electronic health record (EHR) portals can enhance patient and family engagement by providing information and a way to communicate with their healthcare team (HCT). However, portal implementation has been limited to ambulatory settings and met with resistance from HCTs.Objective. We evaluated HCT perceptions before and 6-months after implementation of an inpatient EHR portal application on a tablet computer given to parents of hospitalized children. Methods. This repeated cross-sectional study was conducted with HCT members (nurses, physicians, ancillary staff) on a medical/surgical unit at a quaternary children’s hospital. From December 2014-June 2015, parents of children <12 years old were given a portal application on a tablet computer. It provided real-time vitals, medications, lab results, schedules, education, HCT information and a way to send the HCT messages/requests. HCT members completed surveys pre- and post-implementation regarding their portal perceptions. Pre-post differences in HCT perceptions were compared using chi-squared, Mann-Whitney and Kruskall Wallis tests.Results. Pre-implementation, HCT respondents (N=94) were generally optimistic about the benefits of a portal for parents; however, all anticipated challenges to portal use. Over the next 6-months, 296 parents used the portal, sending 176 requests and 36 messages. Post-implementation, HCT respondent (N=70) perceptions of these challenges were significantly reduced (all p<0.001), including: parents (will) have too many questions (69 vs. 3%, pre-post), parents (will) know results before the HCT (65 vs. 1%), staff (would be/are) skeptical (43 vs. 21%) and there (will be/is) not enough technical support (28 vs. 1%).Conclusions. All HCT respondents anticipated challenges in providing a portal to parents of hospitalized children; however, these concerns were minimized after implementation.
Keywords: Inpatient; pediatrics; engagement; health information technology; personal health record